الإعجاز العلمي بين القبول والرفض - السلومي، أسماء بنت محمد بن عبدالله (عبد الفتاح محمود ادريس, 2016)
There are attempts by contemporary scholars, to show the faces of the scientific miracles in the Book of Allah, and had their reasoning in this way, they tried to reconcile, between the meaning of the Qur'an and modern discoveries in the natural sciences, and self-evident that the contrasting attitude of the scholars interpret the faces of miracles in the book of God, as a result of variation cultural backgrounds and their times, and the breadth of human knowledge circle in the field of cosmic studies, is that some of them overwhelmingly in this matter, and enlist often, and part denied this success, and most of the commentators, who have lived in the last century, did not exaggerate in this matter did not deceive all either way. In this research Nasal this is hawkish stance, and show some isnaads, and recognize the position of scientists from the scientific miracles and all the evidence doctrine, in order to reach the face right in it
ثمة محاولات من العلماء المعاصرين، لبيان وجوه الإعجاز العلمي في كتاب الله تعالى، وكانت لهم اجتهاداتهم في هذا السبيل، فقد حاولوا التوفيق, بين المعنى القرآني والاكتشافات الحديثة في العلوم الطبيعية، وبدهي أن يتباين موقف العلماء من تفسير وجوه الإعجاز العلمي في كتاب الله، نتيجة تباين خلفياتهم الثقافية وأزمانهم, وباتساع دائرة المعرفة الإنسانية في مجال الدراسات الكونية، غير أن قسماً منهم أفرطوا في هذا الأمر، وتكلفوا في كثير من الأحيان, وقسما أنكر هذا التوفيق, ومعظم المفسرين، الذين عاشوا في القرن الأخير, اقتصدوا في هذا الأمر ولم يضلوا عن سواء السبيل. وفي هذا البحث نؤصل هذا الموقف المعتدل, ونظهر بعض أسانيده، ونتعرف على موقف العلماء من هذا الإعجاز العلمي وأدلة كل مذهب, بغية الوصول إلى وجه الحق فيه.
Keywords: الشريعة الإسلامية -- القرآن الكريم -- الإعجاز العلمي -- اللغة العربية -- تفسير القرآن